The experience of medical communication in adults with acute leukemia: Impact of age and attachment security. Issue 1 (12th November 2018) - Fraser, Brooke; Korenblum, Chana; Mah, Kenneth; Watt, Sarah; Malfitano, Carmine; Rydall, Anne; Schimmer, Aaron; Zimmermann, Camilla; Rodin, Gary
Abstract: Background: Health care providers' (HCPs) communication with cancer patients provides both information and support. Younger patient age and greater difficulty accepting support (attachment security) have been linked to poorer communication experiences with HCPs. The present secondary data analysis examined the impact of age group and attachment security on perceived communication problems with HCPs in adults with acute leukemia (AL). Methods: The sample included 95 younger (age < 40 years) and 225 older (age ≥ 40 years) patients with newly diagnosed or recently relapsed AL. We assessed avoidant and anxious attachment security (reluctance to accept support and fear of its unavailability, respectively) with the modified 16‐item Experiences in Close Relationships Scale. The impact of age group and attachment security on perceived communication problems, measured with the Cancer Rehabilitation Evaluation System‐Medical Interaction Subscale, was assessed based on the presence and extent of communication problems. Results: Younger patients (OR = 1.79‐1.82, P  = .030) and those with greater avoidant (OR = 1.44, P  = .001) or anxious attachment (OR = 1.38, P  = .009) were more likely to report communication problems. A similar relationship was found between age (β's = −.17‐.19, P  = .015‐.025), avoidant (β = .29, P  = .013), or anxious attachment (β = .17, P  = .031), and the extent of communication problems. A significant age‐group × avoidant‐attachment interaction (β = −.31, P  = .008) suggested that more avoidant attachment was associated with more perceived communication problems in the younger but not in the older group. Conclusions: Younger patients with AL, especially those more reluctant to seek or accept support, perceive more communication problems with their HCPs than older patients. Greater attention by HCPs to their communication with younger patients is needed.